Healthcare Workers' Perception of Measures to Reduce the Risk of New Tuberculosis Infections: A Qualitative Study Report - Debra Madzinga; Takalani Grace Tshitangano; Ndidzulafhi Selina Raliphaswa; Lufuno Razwiedani (MDPI AG, 2022)
Tuberculosis, which is an infectious airborne disease remained the main leading cause of death in South Africa for three consecutive years from 2016 to 2018. In 2020 alone, the country had an estimated 328,000 people who suffered from TB, with 61,000 dying from it. Collins Chabane Municipality had 129 and 192 new TB cases recorded in 2017 and 2018, respectively, which is far from reaching the END TB STRATEGY targets. WHO scientific evidence demonstrates that TB control measures are effective in reducing the spread and development of new cases. Though scientific evidence revealed negative attitudes towards the recommended TB control measures in public hospitals of the Vhembe district, a deeper understanding of these attitudes is needed to remedy the situation. This study aimed to describe healthcare workers' perceptions of TB control measures at Collins Chabane Municipality in South Africa. A qualitative, exploratory case study design was adopted. Multi-stage sampling technique was used to select both the healthcare facilities and the participants. Only 24 healthcare workers trained on tuberculosis management were voluntarily recruited. However, data were saturated at the twelfth (12) participant purposively selected from six healthcare facilities of Collins Chabane Municipality. Data collected through unstructured in-depth individual interviews were analyzed thematically. The proposal for this study was ethically cleared by the University of Venda Ethics Committee (SHS/20/PDC/35/1111). Results indicate that TB administrative, environmental and respiratory control measures are well understood by health workers even though there are challenges with implementation concerning some, such as closing windows during winter, UVGI lights that are non-functional and taking too long to be fixed, no specimen collection during weekends and holidays thereby delaying TB diagnosis and lack of skills concerning how to use respirators and cough etiquette. The Vhembe district TB control programme should intensify infection control training and continue monitoring giving the needed support.